Export Variety and Country Productivity : Estimating the Monopolistic Competition Model with Endogenous Productivity - Feenstra, Robert; Kee, Hiau Looi (2012)
This paper provides evidence on the monopolistic competition model with heterogeneous firms and endogenous productivity. We show that this model has a well-defined GDP function where relative export variety enters positively, and estimate this function over 48 countries from 1980 to 2000. Average export variety to the United States increases by 3.3% per year, so it nearly doubles over these two decades. The total increase in export variety is associated with a 3.3% average productivity improvement for exporters over the two decades. Overall, the model can explain 31% of the within-country variation in productivity (or 52% for the OECD countries), but only a very small fraction of the between-country variation in productivity.